Nitrate in Gravity Feed System (GFS) water and health risk assessment in Orang Asli Village in Rembau, Negeri Sembilan - Mokhtar, Farhah Nadiah; Adriyani, Retno; Mohd Sham, Shaharuddin (Universiti Putra Malaysia, 2023)
Introduction: To determine the health risk assessment due to exposure to nitrate in Gravity Feed System (GFS) water in the Orang Asli Village of Rembau, Negeri Sembilan. Methods: This study involved 48 respondents who fulfilled the inclusion and exclusion criteria. Respondents with a filtration system installed in their houses were excluded from the study. A modified questionnaire was used to obtain the socio-demographic data. All collected water samples were analyzed using a HANNA Instruments multimeter with an attached nitrate electrode. Results: Nitrate in drinking water did not exceed the maximum limit of 45 mg/L set by health authorities. It ranged from 2.15 to 7.65 mg/L, with a mean ± standard deviation of 4.99 ± 1.37 mg/L. Further to this, the minimum and maximum pH values were 6.57-7.10. It was interpreted that there was no significant association between the concentration of nitrate and pH value in drinking water. The Hazard Quotient (HQ) calculation recorded that all respondents recorded an HQ of less than 1, indicating no cancer risk to consumers. Conclusion: The nitrate levels in GFS water are relatively low and do not threaten human health. However, it is recommended to conduct assessments on a regular basis to guarantee the levels within the permissible limit of the Malaysian National Drinking Water Quality Standard (NDWQS).